Template attacks exploiting static power and application to CMOS lightweight crypto‐hardware. (18th November 2016) - Bellizia, Davide; Djukanovic, Milena; Scotti, Giuseppe; Trifiletti, Alessandro
Summary: A new class of template attacks aiming at recovering the secret key of a cryptographic core from measurements of its static power consumption is presented in this paper. These attacks exploit the dependence of the static current of Complementary metal–oxide–semiconductor Integrated Circuits on the input vector and the maximum likelihood decision rule as a statistical distinguisher. In the proposed Template Attacks Exploiting Static Power (TAESP), we take advantage of the temperature dependence of static currents in order to build a new multivariate approach able to extract relevant information from cryptographic devices. As a validation case study, we consider the PRESENT‐80 block cypher algorithm and its implementation on a 40 nm Complementary metal–oxide–semiconductor process. Monte Carlo and corner simulations at transistor level are used to show the effectiveness of the TAESP in the presence of die‐to‐die and intra‐die process variations. A real attack scenario is then built by adding Gaussian noise to current samples extracted from transistor‐level simulations. The univariate TAESP in which just one temperature is considered to build the templates is compared against the multivariate TAESP in which measurements at different controlled temperatures are exploited. This comparison shows that using just a few different temperatures to build multivariate templates allows to strongly increase the effectiveness of the attack. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : This paper introduces a new class of template attacks aiming at recovering the secret key of a cryptographic core exploiting the dependence of the static current on the input vector of the circuit and the maximum likelihood decision rule. The temperature‐dependence of static currents is exploited to build a multivariate approach able to increase the effectiveness of the attack in presence of process variations. Validation of the approach is based on Monte Carlo simulations of the PRESENT‐80 crypto core.